2007
DOI: 10.2320/matertrans.ma200701
|View full text |Cite
|
Sign up to set email alerts
|

Change in Microstructure and Texture during Annealing of Pure Copper Heavily Deformed by Accumulative Roll Bonding

Abstract: Pure copper sheets were heavily deformed up to equivalent strain of 4.8 by the accumulative roll-bonding (ARB) processed and then annealed. The ARB processed copper showed the ultra-fine grained microstructure which consisted of relatively equiaxed grains having grain thickness of about 0.2 mm. The DSC measurement of the ARB processed specimens revealed that the recrystallization temperature significantly decreased with increasing the number of the ARB cycles. The stored energy did not increase so much at late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…6 consists of a mixture of relatively equiaxed and slightly elongated grains. 12,13) At N ¼ 8, the spacing of high-angle lamellar boundaries of elongated grains was about 370 nm in the present study.…”
Section: )mentioning
confidence: 65%
See 1 more Smart Citation
“…6 consists of a mixture of relatively equiaxed and slightly elongated grains. 12,13) At N ¼ 8, the spacing of high-angle lamellar boundaries of elongated grains was about 370 nm in the present study.…”
Section: )mentioning
confidence: 65%
“…The microstructure of copper at N ¼ 4 possesses the so-called lamellar boundary structure. 12,13) However, the microstructure for N ! 6 consists of a mixture of relatively equiaxed and slightly elongated grains.…”
Section: )mentioning
confidence: 99%
“…Furthermore, in order to compare the grain boundaries in the ARB-Cu with equilibrium grain boundaries, the grain boundary energy and structure of h110i STGBs in pure Cu were computed by molecular dynamics (MD) simulation. The electron back-scattering diffraction (EBSD) measurement in the previous study 14) has found that the ARB-Cu had a texture composed of h110i == TD (the transverse direction of the sheet), so that the present observation of the grain boundary structure by HRTEM was carried out along TD. The grain boundary energy and structure simulation was also done for h110i STGBs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, limiting the thermal expansion of copper is highly desirable as a first step to increase its applicability for thermal management applications. There are number of studies discussing the thermal stability of the microstructure of fine, deformed and severe plastically deformed copper [9][10][11][12][13][14]. However, there are very few reports concerning the thermal expansion of copper.…”
Section: Introductionmentioning
confidence: 96%